Study of Antifungal Property in the Crude Leaf Extract of Ixora coccinea against Botrytis cinerea - Padma Chatterjee, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Study of Antifungal Property in the Crude Leaf Extract of Ixora coccinea against Botrytis cinerea